ANALYSIS OF LANGUAGE POLITICS AND SPEECH ACTIONS IN THE JANUARY 2023 EPISODE OF MATA NAJWA'S TALK SHOW PROGRAM - Malik, Abdul; Kamiri, Kamiri; Goziyah, Goziyah (Universitas Muhammadiyah Tangerang, 2023)
After conducting a content analysis of the January 2023 episode of the Mata Najwa talk show, which consisted of three talk show titles, namely Deliberation Tuntun Sambo Until Candidates for the PSSI Chairperson, the authors drew several conclusions. The speech contained in the January 2023 episode of the Mata Najwa talk show, entitled Deliberation on guiding Sambo to PSSI chairman candidates, contained the use of elements of politeness in the Leech Politeness Principle, for example in the use of the principle of politeness, namely an agreement between the speaker and the hearer and the maxim of humility, because the program Najwa's eyes are speakers and speech partners who have a good education, so they pay great attention to the principle of politeness in speaking